Sustainable intensification and diversification options for enhancing productivity and input use efficiency in eastern IGP of India: Evaluating diversified cropping patterns in Nalanda, Bihar, India - Choudhary, K.M.; Kalvania, Kailash C.; Ali, Shahid; Sinha, Pooja; Kumar, Sanjeev; Jat, R.K.; Bijarniya, Deepak; Krupnik, Timothy J.; Gathala, Mahesh K. (TAFSSA, 2024)
In the eastern Indo-Gangetic Plains (EIGP), agriculture faces significant challenges that directly impact farmers' productivity, profitability, and input use efficiency. The region is heavily dependent on rice and wheat cultivation, but issues such as overreliance on traditional farming practices, inefficient use of water and fertilizers, and limited adoption of modern technologies hinder farm productivity and profit. Moreover, inconsistent irrigation systems, combined with the growing threat of water scarcity, further reduce the efficiency of input use. Climate change has also intensified the vulnerability of crops to floods, droughts, and erratic weather patterns, leading to crop failure or reduced yields. To address these complex changes, the on-farm research was set up by the Transforming Agrifood Systems in South Asia (TAFSSA) Initiative under CIMMYT with the partnership of CGIAR Institutes, JEEVIKA, and the Department of Agriculture in Nalanda district of Bihar, India.